Cholesterol degradation in archaeological pottery mediated by fired clay and fatty acid pro-oxidants - Hammann, Simon; Cramp, Lucy J. E.; Whittle, Mathilda; Evershed, Richard P. (Tetrahedron Letters, 2018)
Cholesterol is generally absent in animal fat residues preserved in archaeological ceramic vessels. It is known from edible oil refining that during bleaching with activated clay sterols are degraded, largely via oxidation. Laboratory heating experiments using fired clay from replica pottery vessels promoted rapid degradation of cholesterol via oxidation. Furthermore, heating cholesterol with fatty acids (saturated and unsaturated) revealed additional degradation to occur independently of the ceramic matrix. As both conditions are met in archaeological pottery during animal (and plant) product processing involving heating, the very rare detection of sterols in organic residues can be explained.
Keywords: Archaeology; Fatty acids; Fired Clay; Cholesterol; Degradation; Organic residues